Analysis of Output Voltage in Contact Separation Triboelectric Nanogenerator with Frequency Variation and its Suitability in Ships: A Numerical Calculation-Based Study - Ede Mehta Wardhana; Agoes Ahmad Masroeri; Brivo Rafanki (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2024)
Triboelectric Nanogenerator (TENG) is an innovative technology that harnesses the triboelectrification phenomenon to generate electricity through the Contact Separation mode, where two materials with triboelectric properties interact. TENG can generate electricity at low frequencies. In the context of ship engine vibrations, the application of TENG with the Contact Separation mode can convert mechanical vibration energy from vibrations generated in the ship engine room into additional electrical power sources. The principle of TENG operation focuses on changes in triboelectric charge during the contact, separation, and compression processes. This study uses parameters commonly encountered in ships, namely low-frequency vibrations, as well as limitations imposed by classifications and regulations on these vibrations. Parameters used to analyze suitable modes for application in ships vary, namely frequencies ranging from 1 to 30 Hz and displacement distances ranging from 0.5 to 2 mm with intervals of 0.5 mm, resulting in voltages ranging from 0.01 to 1.55 V. After obtaining suitable modes, this study will match the modes for application on ships with a frequency of 50 Hz and displacement distances varied from 7 to 25 mm using FEP and Silicone materials, resulting in voltages ranging from 13.20 to 249.20 V. The results of this research can provide guidance for the development of TENG technology on ship engines to enhance energy efficiency and sustainability in the maritime sector.